Commercial sharks under scrutiny: Baseline genetic distinctiveness supports structured populations of small-spotted catsharks in the Mediterranean Sea - Melis, Riccardo; Vacca, Laura; Cariani, Alessia; Carugati, Laura; Cau, Alessandro; Charilaou, Charis; Di Crescenzo, Simone; Ferrari, Alice; Follesa, Maria Cristina; Hemida, Farid; Helyar, Sarah; Lo Brutto, Sabrina; et al. (Frontiers in Marine Science, 2023)
The present study, based on microsatellite markers, describes a population genetic analysis of the small-spotted catshark Scyliorhinus canicula (Linnaeus, 1758), representing one of the most abundant and commonly caught cartilaginous fishes in the Mediterranean Sea and adjacent areas. The analyses were performed to unravel the genetic features (variability, connectivity, sex-biased dispersal) of their relative geographic populations, both at the small (around the coast of Sardinia, Western Mediterranean Sea) and at a larger spatial scale (pan-Mediterranean level and between the Atlantic Ocean and the Mediterranean Sea). Individual clustering, multivariate and variance analyses rejected the hypothesis of genetic homogeneity, with significant genetic differences mainly within the Mediterranean between the Western and Eastern basins, as well as between the Mediterranean and the NE Atlantic Ocean. In detail, our results seem to confirm that the Strait of Gibraltar could not represent a complete barrier to the exchange of individuals of small-spotted catshark between the Atlantic Ocean and the Mediterranean Sea. In the latter area, a complex genetic structuring for S. canicula was found. Apart from differences among the Western, Eastern and Adriatic sites, within the Western basin the small-spotted catsharks around Sardinian waters are strongly differentiated from all others (both from the eastern Tyrrhenian Sea and southernmost part of the Algerian basin) and are demographically stable. Several possible mechanisms, both biological and abiotic (e.g., migratory behavior, waterfronts, and oceanographic discontinuities), are discussed here to explain their peculiar characteristics. Overall, the genetic data presented, both at the local and regional level, could represent a baseline information, useful for the temporal monitoring of populations, and to assess the effects of present or future fishing/management/conservation measures.